Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Usahatani Cabai Merah di Kecamatan Siborongborong Kabupaten Tapanuli Utara - Jumaguni, Naomi; Handayani, Migie; Setiadi, Agus (Universitas Galuh, 2024)
Curly red chili is a horticultural commodity with high economic value in Indonesia. High economic value is a motivation for curly red chili farmers in running their farming business to get maximum income. The size of the curly red chili farmers income can be influenced by certain factors. This research aimed to analyze income and analyze the factors that influence curly red chili farming income in Siborongborong District, North Tapanuli Regency. This research was conducted in December 2022-Februari 2023 in Siborongborong District. The research location was determined purposively based on the consideration that the amount of curly red chili production in the Siborongborong District was the highest production in North Tapanuli Regency. The research method used in this study is the survey method. The sample was determined through the census method by taking the entire population of 54 farmers. The data analysis method used were the analysis of production costs, revenue, income, R/C ratio, and multiple linear regression. The results showed that the average of total income of curly red chili farmers in Siborongborong District per planting season was Rp 34.164.744,99 with a R/C ratio of 1,84. The variables of land area, labor outpouring, seed costs, fertilizer costs, pesticide costs, production amounts, and selling prices simultaneously affect curly red chili farming income. The variables of seed costs and pesticide costs partially do not affect curly red chili farming income, while the variables of land area, labor outpouring, fertilizer costs, production amounts, and selling prices affect curly red chili farming income.